Assessing the rates of false-positive ovarian cancer screenings and surgical interventions associated with screening tools: a systematic review - Sierra M Silverwood; Grant Backer; Annie Galloway; Katrina Reid; Anna Jeter; Margo Harrison (BMJ Oncology)
Objective Early detection of ovarian cancer can improve patient outcomes; however, screening tests can yield false-positive results, leading to unnecessary surgical interventions. This systematic review explores the prevalence of false-positive ovarian cancer screenings and subsequent unnecessary surgical interventions.Methods and analysis Five databases were searched in March 2023 and again in March 2024, encompassing primary literature published between 2003 and 2024. Data collection focused on studies reporting the number of surgical interventions resulting from a false-positive screening result. Studies were categorized by patient risk (average vs high). Studies lacking screening or surgical intervention data, those in which the screening did not directly influence surgical decisions, or those not in English were excluded.Results Of the 12 papers included, the majority were cohort studies (75%) based in the USA (66%). The primary screening methods included Cancer antigen 125 and transvaginal ultrasound scanning. Patients were stratified by risk, with four studies focused on high-risk populations and eight in average-risk populations. The false-positive and surgical screening rates exhibited significant variability, regardless of risk (0.1%–23.3% and 0%–54.9%, respectively). Complications associated with unnecessary surgical interventions, such as perforation, blood loss and bowel injury, were only reported in four studies. No studies examined the effect these interventions had on patients’ quality of life or directly reported the associated costs of these interventions.Conclusion This review highlights the significant variability in ovarian cancer screening results, which lead to unnecessary and invasive surgical procedures causing complications such as perforation, blood loss and bowel injury.